Zhanwen lichang, bu wang jieji douzheng. Tigao jingti, jin wo geming qianggan - Zhang Xueyin
'Take a firm stand, do not forget class struggle. Enhance your vigilance, firmly grasp the arms of revolution.' Printno. 8146.925.